2015
DOI: 10.1016/j.amsu.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality-of-Life in a cohort undergoing cholecystectomy

Abstract: IntroductionPatient-related outcome measures are crucial when assessing outcome from surgical intervention registers. The aim of this study was to analyse what factors affect Health-Related Quality of Life (HRQoL) in patients undergoing cholecystectomy, and to assess the feasibility of SF-36 as a HRQoL instrument in a patient register.MethodsThe SF-36 questionnaire was distributed to patients preoperatively and 6–9 months after surgery. The outcome of patients who had undergone planned surgery between January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“… 1 There are some limited and inconsistent information available about the long-term quality of life in these patients. 2 In previous studies, female gender and cholecystectomy for gallstone colic correlated with low quality of life scores. Female gender also correlated with a higher risk of pain in the right upper stomach quadrant after cholecystectomy.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“… 1 There are some limited and inconsistent information available about the long-term quality of life in these patients. 2 In previous studies, female gender and cholecystectomy for gallstone colic correlated with low quality of life scores. Female gender also correlated with a higher risk of pain in the right upper stomach quadrant after cholecystectomy.…”
Section: Introductionmentioning
confidence: 86%
“…There are some limited and inconsistent information available about the long-term quality of life in these patients 2. In previous studies, female gender and cholecystectomy for gallstone colic correlated with low quality of life scores.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, the surgical technique has developed during this period, which may also have biased the outcome. The SF-36 instrument is routinely used for assessing quality of life in patients undergoing gallstone surgery in the Swedish national register for gallstone surgery [25], [26]. Since the start of GallRiks 2005, the perceived QoL measured with SF-36 has remained relatively stable [25].…”
Section: Discussionmentioning
confidence: 99%
“…This positive result following cholecystectomy is consistent with previous published literature. [ 11 , 12 , 24 , 31 ] In the case of severe complication such as BDI, several studies reported that extremely long-term follow-up of 8 to 12 years was needed to improve QoL after cholecystectomy. [ 14 , 32 , 33 ] Also, other studies suggested that the occurrence of a BDI has a great impact on the patient's physical and mental QoL even after excellent functional outcome following repair.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] However, there is limited and inconsistent information available about PRO in these patients. [ 23 , 24 ] For these reasons, the clinical management of these patients is frequently without an evidence-based approach. The purpose of this prospective multicenter observational study is to analyze which factors have the greatest impact on short- and long-term PRO including various postoperative symptoms and QoL using the GIQLI questionnaire following cholecystectomy.…”
Section: Introductionmentioning
confidence: 99%